Modo 401 font & text courseware - Ablan, Dan.; Safari eBooks ([S.l.] : 3D Garage.com : AGA Digital Studios, 2010)
"We all know modo 401 is an amazing 3D modeling, texturing, and rendering application. You can create lifelike 3D models, and animations of just about anything you want. But what about text? We're not talking your typical flying logos here, but the stuff you see everyday like those created for NFL, NBC, and Fox television. Learn how to not only use the text tool to its fullest extent, but how to incorporate modo's amazing modeling and surfacing tools to create those astounding broadcast animations you've been wanting to create. This 6-hour course is all you need to model, texture, light, animate and render killer text and fonts in modo 401."--Resource description page.
Title from title screen.
Keywords: Computer animation -- Software; Three-dimensional imaging; Computer fonts; Electronic books